2021
DOI: 10.52403/ijshr.20210459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myofascial Release Technique in Plantar Fasciitis on Pain and Function- An Evidence Based Study

Abstract: Background: Plantar fasciitis is a common cause of pain in the heel which occurs as a result of inflammation of the plantar aponeurosis at its attachment on the calcaneal tuberosity. Myofascial Release Technique is intended to improve the mobility of soft tissue through application of a slow, controlled mechanical stress directly into a restriction. Pressure is gradually increased or repeated until the mobility of the tissue is felt to improve. Purpose: The purpose is to study the scientific evidences regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…According to Tandel and Shukla (2) , fascia and connective tissues often move with little constraint under normal circumstances. Fascial tissue length and suppleness are hypothesised to diminish as a result of physical damage, repetitive strain injury, and inflammation, leading to fascial constriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Tandel and Shukla (2) , fascia and connective tissues often move with little constraint under normal circumstances. Fascial tissue length and suppleness are hypothesised to diminish as a result of physical damage, repetitive strain injury, and inflammation, leading to fascial constriction.…”
Section: Discussionmentioning
confidence: 99%
“…Plantar fasciitis is a condition that develops as a result of recurrent stress to the plantar fascia at its calcaneal insertion (2) . This explanation can be used to explain around 15% of all foot issues that require medical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, in addition to the restriction of physical activities in individuals due to the pain that occurs due to this disease, individuals are negatively affected both socially and psychologically due to these problems, and their quality-of-life decreases (12). On the other hand, PF has a negative impact on various aspects of the individual's ADL, as well as on sports and leisure time (especially active recreational activities) activities (13,14). As well as our knowledge, there was no study that examines on relationship between quality of life and activity performance and satisfaction levels in ADL in individuals with PF.…”
Section: Introductionmentioning
confidence: 99%
“…Satish C pant et al conducted a comparative study on the effect of Myofascial Release And Stretching Exercises on plantar fasciitis and found that both myofascial release and stretching exercises are effective in treating patients with plantar fasciitis27 . Another study was done by P Sivasankar to find out effect of ultrasound therapy and Myofascial Release on pain and function in patients with plantar fasciitis and concluded that both ultrasound therapy and myofascial release is effective on pain and function in patients with plantar fasciitis28 . Heni Ishwarlal Tandel and Yagna Unmesh Shukla did a evidenced based study to find out effect of Myofascial Release Technique in plantar fasciitis on pain and function.…”
mentioning
confidence: 99%